Human reasoning on social interactions in ecological contexts: insights from the theory of mind brain circuits - Isernia, Sara; Pirastru, Alice; Rossetto, Federica; Cacciatore, Diego Michael; Cazzoli, Marta; Blasi, Valeria; Baksh, R. Asaad; MacPherson, Sarah E.; Baglio, Francesca (Frontiers in Neuroscience, 2024)
The relationship between neural social cognition patterns and performance on social cognition tasks in daily life is a topic of debate, with key consideration given to the extent to which theory of mind (ToM) brain circuits share properties reflecting everyday social functioning. To test the efficacy of ecological stimuli in eliciting brain activation within the ToM brain circuits we adapted the Edinburgh Social Cognition test social scenarios, consisting of dynamic ecological contextually-embedded social stimuli, to a fMRI paradigm.Methods: Forty-two adults (21 males, mean age ± SD = 34.19 years ± 12.57) were enrolled and underwent an fMRI assessment which consisted of a ToM task using the Edinburgh Social Cognition test scenarios. We used the same stimuli to prompt implicit (movie viewing) and explicit (silent and two-choice answers) reasoning on cognitive and affective mental states. The fMRI analysis was based on the classical random effect analysis.Group inferences were complemented with supplemental analyses using overlap maps to assess inter-subject variability.We found that explicit mentalizing reasoning yielded wider neural activations when two-choices answers were used. We also observed that the nature of ToM reasoning, i.e., affective or cognitive, played a significant role in activating different neural circuits.Discussion: The ESCoT stimuli were particularly effective in evoking ToM core neural underpinnings and elicited executive frontal loops. Future works may employ the task in clinical setting to investigate ToM network reorganization and plasticity.